MMLIBB DC-DC converter: a novel modular, multi-level, interleaved-based, bidirectional topology - Monteiro, Vítor Duarte Fernandes (2023)
The extent of applications that claims the use of power electronics systems is cumulative, deriving innovative topologies from the classical topologies, and diversifying the requisites for innovative topologies, such as the need for multiple inputs/outputs. In addition, prerequisites such as high efficiency, modularity, bidirectionality, low ripple, high voltage and/or high current interfaces, high frequency, and low cost are pushing the necessity of new power electronics topologies. Aligned with this vision, a new topology is proposed. Due to its structure, the modular, multi-level, interleaved-based, bidirectional (MMLIBB) DC-DC converter topology can be utilized for various purposes, such as the interface of renewables and/or energy storage elements with multiple DC interfaces and hybrid AC/DC grids. The MMLIBB topology operates in bidirectional mode and has a modular structure, which easily incorporates additional sub-modules for increasing the number of DC interfaces. Likewise, as the number of added sub-modules increases, the number of multilevel voltages rises, and the ripple current declines. The proposed topology can operate with the classical current or voltage control, though the modulation must be very specific, and hence, a comprehensive attention is given to that in this paper. The characteristics of the MMLIBB topology are proven based on simulations obtained for decisive operating situations.